Microplastic Occurrence in Corbicula sp. Collected from Ba Be Reservoir: Characteristics and Potential Risks - Thi Oanh, Doan; Thi My, Nguyen; Thi Anh Nguyet, Nguyen; Phuong Thao, Pham; Le Anh, Pham; Thuy Duong, Nguyen; Van Huong, Nguyen; Thi Phuong Quynh, Le; Thi Thu Ha, Pham; Van Manh, Do; Thi Thuy, Duong (VNU Journal of Science: Earth and Environmental Sciences, 2025)
The prevalence of microplastic contamination is widespread in freshwater ecosystems, including rivers, lakes, and reservoirs. Benthic organisms are exposed to a wide range of dangers due to the presence of microplastic particles, which can be found in sediments and aquatic environments. Although the distribution of microplastics in aquatic systems has been extensively studied worldwide, research on their occurrence in bivalves from Vietnamese reservoirs is limited. This study presents the results of microplastic (MP) presence in freshwater clams Corbicula sp. in Ba Be Reservoir, Thai Nguyen Province, Vietnam. Clam samples were collected at sites representing different levels of human activity, including areas near concentrated tourism and residential zones, as well as those far from such zones. Microplastics were found in all clam samples, with densities ranging from 5 to 11 items/individual and from 2.94 to 5.92 items/g wet weight. Fibers were the most abundant type of microplastic, with predominant sizes ranging from 300 to 1,000 µm. White and black microplastics were the most dominant colors. The main detected polymers were polypropylene, polyethylene terephthalate, and polyethylene. These findings provide an important baseline dataset, warning of a potential risk to the food chain and the health related to the Ba Be Reservoir ecosystem.